Dominance of leadership style and preventive work discipline in improving the performance of village apparatus - Komala, Nina; Junaenah, Junaenah; Syarifah, Syarifah; Awaludin, Jamal Fahrul; Haryadi, Didit (Trigin Publisher, 2024)
Performance is an important factor that affects success. In an organization, this is one of the most important functions of an agency. This study aims to determine the variables that affect the performance of village apparatus and develop a theoretical basis and research model. This study used an associative descriptive quantitative method with 30 respondents drawn into samples using non-probability sampling and saturated sampling / total sampling. Data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis of leadership style does not affect the performance of the village apparatus. Thus, the second hypothesis states that work discipline significantly influences the performance of the village apparatus. The third hypothesis is that the performance of the village apparatus is influenced by leadership style and preventive work discipline, which can simultaneously improve the acceleration of the performance of the village apparatus. This research is expected to make theoretical contributions to the literature in this context, certainly in the context of human resource management.